When we were young : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family., 2018)
"From #1 New York Times bestselling author Karen Kingsbury comes a classic story about second chances, featuring the beloved Baxter family and a young father who finds his whole world turned upside down on the eve of his divorce"--